Strategi Komunikasi Berbasis Multimedia dalam Pendidikan Jarak Jauh pada Mata Kuliah Atletik - Suci Lukitowati; Andika Triansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to produce good learning videos through the application of various communication strategies. This learning video can be used as a distance learning supplement for athletic subjects. The research procedure adapted the ADDIE model developed by Robert Maribe Brach, consisting of analysis, design, development, implementation, and evaluation. The analysis process is carried out by determining the communication strategy. The communication strategy consisted of a communicator selection strategy, a learning video audience determination strategy, a message determination strategy, a media determination strategy, a message effect determination strategy, and a message evaluation strategy. Product testing at the implementation stage was carried out on students of the Physical Education study program, Faculty of Teacher Training and Education, Tanjungpura University. The data collection instrument used was a questionnaire sheet which was then given to material and media experts to assess the feasibility of the resulting product, a student response questionnaire sheet to assess user acceptance / response and a questionnaire sheet to determine the effect of the product produced. The data analysis technique used is quantitative and descriptive qualitative analysis. The research resulted in a product in the form of multimedia learning videos in Mp4 format. With the validity value of material expert 3.6 (very good) and media expert 3.4 (good). Student response with a score of 3.4 (good) and an effect size of 1.09 (high). The conclusions from the results of research on the development of multimedia learning videos are proven to be used as a supplement that can increase student curiosity, interest, attention and ease in understanding the material being studied so as to contribute to improving learning outcomes. Keywords: Communication Strategy, Distance Education, Athletics, Multimedia